INTERPRETASI DATA ANOMALI MEDAN MAGNETIK UNTUK MENGIDENTIFIKASI PENINGGALAN KADIPATEN PASIR LUHUR DESA TAMANSARI KARANGLEWAS - Riza Arfian Susanto; Sehah Sehah; Zaroh Irayani (Jurnal Pendidikan Fisika, 2017)
Magnetic surveying have been done in the area around of the Carangandul site, District of Karang lewas, Regent of Banyumas. The research purpose is for identify Kadipaten Pasir Luhur’s remainder whom maybe buried at around that sites. The total magnetic intensity data obtained, then be processed, corrected, and reduced so thatbe obtained the local magnetic anomaly data. Modeling process to magnetic anomaly data with two dimensions (2D) have been done by utilize Mag2DC for windows software. Based on the modeling results, be obtained the subsurface lithology section with magnetic susceptibility values of 0.0141 – 0.0626 cgs units. The interpretation ofmodeling resultsshow thatin the depth of 0 – 10 meters be found the sand stone, then in the depth of 10 – 125 meters befound the breccia-andesite rocks, then in the depth of 125 – 250 meters be found the andesite rocks with insert of sand, and then in the depth of 250–500 meters be found two pieces of rocks i.e. breccia-andesite and andesite-basaltic from volcanic lava boulder of Slamet Volcano which be estimated as the basement inthe research area. Based on the interpretation resultis not found available distribution of pure andesite as sites that exist on the surface.